Model Teams Games Tournament Berbantuan Quizizz Paper Mode untuk Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Citra, Della; Mulyono, Dodik; Rosalina, Elya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the mathematics learning outcomes of fourth-grade students at SD Negeri 04 Lubuklinggau after implementing the Teams Games Tournament learning model with the Quizizz Paper Mode. The research method used was a pre-experimental design with a one-group pretest-posttest. The results showed that the t-test analysis obtained t_(calculated)(3.70) ≥ t_(table) = (1.713), thus Ho is rejected, and Ha is accepted. The conclusion is that implementing the Teams Games Tournament learning model with Quizizz Paper Mode significantly improved the mathematics learning outcomes of fourth-grade students at SD Negeri 04 Lubuklinggau, achieving the KKTP (Qualified Competency Standard). Keywords: Mathematics Learning Outcomes, Model, TGT, Quizizz Paper Mode